PENGARUH MEDIA POSTER COMMENT DIGITAL TERHADAP KETERAMPILAN ABAD 21 DALAM PEMBELAJARAN FIQIH BERBASIS PROYEK - Zainurroyyan; Chodidjah Makarim; Noneng Siti Rosidah (KOLONI, 2022)
The rapid development of science and technology in the 21st century will have consequences on the huge of challenges that are different from those that have been faced before. Educational institutions are challenged to find ways to enable students to succeed at work and in life through mastering creative thinking skills, flexible problem solving, collaboration and innovation. One of the learning methods offered is the use of the digital comment poster media method combined with project-based learning that is process-centered, timed, and problem-focused, very helpful in achieving learning objectives. The purpose of this study is to determine the effect of digital comment poster media project-based method with conventional method in fiqh subject at the Al Sudais Indonesia Foundation. This study uses a quantitative research approach. This type of research is experimental. Collecting data using tests (pretest and posttest). The result of this study were seen from the paired sample t test and independent sample t test. From the posttest results obtained, with an average value of 77 for the experimental class and 71 for the control class, it can be concluded that the application of the Digital Poster Comment method in the learning process has an influence on student learning outcomes. Keywords: Digital Comment Poster Media, Fiqh Subject, Project